A thermoelectric device for ophthalmic heat flux density measurements: results of piloting in healthy individuals - Anatychuk, L.; Pasyechnikova, N.; Naumenko, V.; Zadorozhnyy, O.; Kobylianskyi, R.; Gavrilyuk, N. (Oftalmologicheskiĭ zhurnal., 2019)
Background: Assessment of heat exchange processes in the human body is based on temperature and heat flux measurements. Today, there is no instrument for measuring the heat flux density from the eye. Purpose: To investigate the heat flux density from the ocular surface in healthy individuals using the developed thermoelectric device. Materials and Methods: The thermoelectric device for the measurement of heat flux from the eye has been developed within the framework of the partnership agreement between the Institute of Thermoelectricity and the Filatov Institute. Thirty-two healthy individuals (64 eyes) were under observation. Participants were divided into three age groups. They underwent a bilateral eye examination which included measurements of intraocular pressure, temperature of the external corneal surface, and heat flux density from the eye. Results: Mean room temperature during examination sessions was 21.3 ± 0.8 °С. In addition, mean temperature of the external ocular surface and mean heat flux density from the human eye were 34.6 ± 0.7°С and 7.7 ± 1.3 mW/cm2, respectively. We found that the heat flux density from the eye decreased with age in healthy subjects. Conclusion: The first ever thermoelectric device for real-time measuring of the heat flux density from the human eye was developed. The developed device was used to measure the heat flux density from the eye in healthy subjects, and to demonstrate the relationships of this characteristic with the temperature of the external ocular surface and subject age.